AVAILABILITY OF PEDIATRIC FORMULATIONS FOR THE 100 MOST PRESCRIBED DRUGS IN PEDIATRIC AMBULATORY CARE – 2002 VS. 2010. Issue 1 (14th December 2015) - Ziesenitz, Victoria C.; Anker, Johannes N. van den; Amirshahi, Maryann
Abstract : Introduction: US legislative efforts over the past two decades have attempted to promote therapeutic equity for the pediatric population. The objective of this study was to explore trends in the availability of pediatric formulations for the most commonly prescribed drugs in US pediatric ambulatory care. Methods: A retrospective review of the CDC's National Ambulatory Care Survey (NAMCS) from 2002–10 was performed focusing on visits involving children<6 years. The top 100 medications prescribed for which an oral dosage form was available were identified. The availability of a pediatric specific formulation was determined from FDA labeling data. Trends were compared between 2002 and 2010. Results: In total, 94, 152, 217 prescriptions in 2002 and 2010 were analyzed. The most often prescribed drugs were anti-infectives (52.8 vs. 41.6%), respiratory agents (19.2 vs. 21.7%) and antipyretics/ analgesics (14.6 vs. 21.1%). In 2002, a pediatric formulation was available for 94.4% of prescriptions in comparison 95.5% in 2010 (p<0.05). Pediatric formulations were more commonly available for anti-infectives (95.3 vs. 95.9%), antipyretics/ analgesics (99.8 vs. 99.4%) as well as for respiratory (99.5 vs. 98.7%), endocrinologic (80.2 vs. 95.7%), and gastrointestinal (92.6 vs. 97.9%) agents, whereas pediatric formulations were lacking for cardiovascular (68.0 vs. 52.1%), neurologic (46.6 vs. 55.2%) and psychotherapeutic drugs (76.3 vs. 66.1%, all p<0.05). Conclusion: Since the US Best Pharmaceuticals for Children Act 2002, more pediatric specific formulations have become available. Anti-infective agents, respiratory agents and antipyretics/analgesics have been the most commonly prescribed drugs in children <6 years.